A Simple Command to Calculate Travel Distance and Travel Time. (January 2018) - Weber, Sylvain; Péclat, Martin
Obtaining the routing distance between two addresses should not be a hassle with current technology. Unfortunately, this is more complicated than it first seems. Recently, several commands have been implemented for this purpose (traveltime, traveltime3, mqtime, osrmtime ), but most of them became obsolete only a few months after their introduction or appear complicated to use. In this article, we introduce the community-contributed commandgeoroute, which retrieves travel distance and travel time between two points defined either by their addresses or by their geographical coordinates. Compared with other existing commands, it is simple to use, efficient in terms of computational speed, and versatile regarding the information that can be provided as input.